Research trends and hotspots of high tibial osteotomy in two decades (from 2001 to 2020): a bibliometric analysis - Zhang, Haitao (J Orthop Surg Res, 2020)
BACKGROUND: The purpose of this study is to comprehensively analyze the global application trend of high tibial osteotomy (HTO) and identify promising research hotspots of HTO based on bibliometrics and visual analysis. METHODS: Publications (articles and reviews) related to HTO from 2001 to 2020 were retrieved from the Web of Science Core Collection database (WOSCC). The country, institution, year, author, journal, average citations per item, H index, title, abstract, keywords of publication, and the top 10 cited articles were extracted and analyzed in detail. The VOSviewer software was used to analyze theco-occurrence of keywords to predict the hotspots of HTO. RESULTS: A total of 1883 articles were included. In the past 20 years, the number of HTO articles has shown an increasing trend in general. The top 3 countries (the USA, Germany, and South Korea) accounted for 49.547% of all articles published. The USA has the largest number of publications. The University of Western Ontario is the largest contributor. The Knee Surgery Sports Traumatology Arthroscopy is the most influential journal. Professors Saito T and Imhoff AB are the leading scholars who made great achievements in the HTO field. The research direction can be divided into the following 5 clusters: "prognosis and outcome", "HTO combined with cartilage restoration techniques", "animal experimental research", "study on bone union and plate fixation at osteotomy", and "surgical technique research". CONCLUSION: In terms of the trend of previous years, an increasing number of literatures related to HTO will be published in the future. The USA is a world leader in the field of HTO. South Korea presented great potential in this area. HTO combined with cartilage restoration techniques, postoperative prognosis and outcome, and surgical technique research may be the future hotspots in the field of HTO research.